Validation of the Sleep Hygiene Index for Peruvian Higher Education Students - Linares Weilg, Jorge Luis (2025)
The Sleep Hygiene Index is an instrument created in the United States with the purpose of evaluating the behaviors related to the sleep time of university students, it was later adapted in Peru for the population of older adults, having been translated, modified, validated by experts and evaluated through internal consistency analysis. The present study aims to validate the instrument for peruvian higher education students. The design was based on a structural equation model and confirmatory factor analysis. The results showed adequate values for all indices: validation by expert judgment (V = .92), semantic validation (V = .95), reliability indices (α = .750; Ω = .783), model fit indices (GFI = .971, CFI = .964, RMSEA = .042, SRMR = .039, PARSIMONY: PNFI = .695, PGFI = .600, CMIN/DF = 1.711). It is concluded that the validated instrument allows to adequately collect and quantify sleep-related behaviors in peruvian higher education students.